Effect of Permanent Load in Gresik Alluvium on Friction Pile Embedment Depth - James Oetomo; Ahmad Sulaiman; Ryan Achmad Fadhillah; Eka Diah Astuti (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Hydrostatic load, approximately 250-35 kPa (i.e., water of 2.5m-3.5m high), has been applied in the project area for about 25 years; hereafter, it will be referred as permanent load. Recently, this permanent load including its perimeter embankment, is demolished for which a new facility will be built. The upper 2-4m soil layer in this area consists of fill soil (mainly cohesionless material) overlying thick Gresik alluvium layer. A bearing layer was not found (down to an investigation depth of 50m). The initial design of pile embedment depth refers to the legacy soil report, pile embedment information from the surrounding area (not being subjected by permanent load), and preliminary soil investigation data (from the surrounding area); in this case, the projected embedment depth is 20-23m with the friction pile design concept. Due to the proximity of project location with existing facilities, the jacking-driven pile method, with HSPD (Hydraulic Static Pile Driver) machine, is selected for installing the precast spun pile. The pile jacking works indicate that piles can only be driven down to a depth of about 12m (far less than the projected depth). This paper provides an analysis on the changes of soil properties due to permanent load, which in turn increasing the pile shaft capacity and effectively reducing the pile embedment depth. The analysis is supported by data from pile jacking record, PDA test, and instrumented test pile. Discussion regarding the conservatism in pile design is also presented.